Enlarged cardiophrenic lymph nodes predict disease involvement of the upper abdomen and the outcome of primary surgical debulking in advanced ovarian cancer - Luger, Anna K. (Acta Obstet Gynecol Scand, 2020)
INTRODUCTION: The outcome of ovarian cancer patients is highly dependent on the success of primary debulking surgery in terms of postoperative residual disease. This study critically evaluates the clinical impact of preoperative radiologic assessment of the cardiophrenic lymph node (CPLN) status in advanced ovarian cancer. MATERIAL AND METHODS: Baseline CT scans of 178 stage III and IV ovarian cancer patients were retrospectively reviewed by two independent radiologists. CPLN enlargement defined at a short‐axis ≥5 mm was evaluated for its prognostic value and predictive power of upper abdominal tumor involvement and the chance of complete intra‐abdominal tumor resection at primary debulking surgery. Only patients without surgically removed CPLN were eligible for this study. RESULTS: Enlarged CPLNs were detected in 50% of patients and correlated with radiologically suspicious (P = .028) and histologically confirmed (P = .001) paraaortic lymph node metastases. CPLNs ≥ 5 mm were associated with high CA‐125 levels at baseline and revealed independent prognostic relevance for progression‐free survival (hazard ratio [HR] 2.14, 95% confidence interval [CI] 1.33‐3.42) and overall survival (HR 2.18, 95% CI 1.16‐4.08). Noteworthy, patients with enlarged CPLNs nonetheless benefit from complete intra‐abdominal tumor debulking in terms of an improvement in progression‐free survival (HR 0.60, 95% CI 0.38‐0.94) and overall survival (HR 0.59, 95% CI 0.35‐0.82). Enlarged CPLNs correctly predicted carcinomatosis of the upper abdomen in 94.6%. A predictive score of complete tumor debulking, termed CD‐score, which integrates, beside a CPLN short axis <5 mm, an ascites volume <500 mL, and CA‐125 levels <500 U/mL at baseline, correctly predicted complete intra‐abdominal debulking in 100% of patients. CONCLUSIONS: CPLNs ≥5 mm predict upper abdominal tumor involvement. The application of the CD‐score predicted complete macroscopic tumor resection at primary surgery in all of the patients. Although, CPLN pathology suggests extra‐abdominal disease, we consistently demonstrated that patients nonetheless benefit from complete intra‐abdominal tumor resection.